Solutions for the Development of Vietnamese Culture and People - Hoang Nam, Nguyen (International Journal of Educational and Life Sciences, 2024)
This paper provides a detailed analysis of the current state and challenges in the development of Vietnamese culture and people. Using qualitative research methods, including in-depth interviews, surveys, and document analysis, the paper comprehensively evaluates the present issues. Based on these evaluations, the paper proposes key solutions to enhance and promote the sustainable development of Vietnamese culture and people in the coming period. These solutions focus not only on preserving and promoting traditional cultural values but also on adapting to the new demands of modern society, contributing to the construction of a diverse and rich culture, and improving the quality of life for the people.